PMU-PKM di Kecamatan Manggala Kota Makassar - Asri Usman; Muh Sobarsyah; Bakhtiar Mustari (Jurnal Pengabdian Masyarakat Hasanuddin (JPMH), 2021)
The service is carried out because the owners and perpetrators of MSME business groups in the Manggala District have not been fully understood how to properly manage finances in developing the business they are involved in. Basically, the financial management of MSME actors is still minimal in theory and practice due to lack of training and knowledge from MSME actors/owners related to how to manage finances according to the needs in developing MSMEs. The results of the initial data collection of the service team in early 2021 the number of MSMEs in the Manggala sub-district ranged from 100 MSMEs of which around 50 MSMEs were involved in the mushroom business, of which almost 100% of financial management and management were still very minimal and did not meet the standards to be used as tools for receive capital assistance in developing the business they are engaged in. This condition is because most of the MSME financial managers with the highest education level are high school graduates (SMA) who have never been fully engaged in how to manage finances in MSMEs that meet standards. Thus, there are 2 problems experienced by MSME actors in the Manggala sub-district, Makassar Municipality, namely HR competence and MSME financial management.